The significance of early Permian and early Carboniferous U–Pb zircon ages in the Bossòst and Lys‐Caillaouas granitoids (Pyrenean Axial Zone). (8th August 2018) - Lopez‐Sanchez, Marco A.; García‐Sansegundo, Joaquín; Martínez, Francisco J.
Abstract : The Axial Zone of the Alpine Pyrenees exposes Ediacaran‐Palaeozoic metasediments and orthogneisses intruded by abundant Variscan granitoids that resulted in elongated HT metamorphic domes separated by tight synforms with low‐grade metasediments. Yet, the age of the granitoids within the metamorphic domes remains debated, hindering the correlation of Variscan deformation stages and the HT metamorphism between the different domes. Here, we dated two granitoids located within classical metamorphic domes using U–Pb LA‐ICP‐MS zircon geochronology: the Bossòst and the Lys‐Caillaouas granitoids in the Garona and Lys‐Caillaouas domes, respectively. The results indicate that the leucogranitic facies of both granitoids have Early Permian crystallization ages at 295 ± 2 Ma and 297 ± 2 Ma, respectively. Furthermore, we found a small population of inherited zircon with Serpukhovian (331–323 Ma) ages in the Lys‐Caillaouas granitoid, reinforcing the existence of an elusive but widespread early Carboniferous magmatic event in the Pyrenees. These ages discard two previous hypotheses explaining the age disparity observed in the different domes: either that the HT‐LP metamorphism is of Visean age only or that the dome formation was diachronous along the Axial Zone, ranging from Visean in the central part to late Carboniferous in the eastern Axial Zone. The early Permian age found in the leucogranitic facies of the Bossòst granitoid questions the proposed Visean age for the formation of the Garona dome and the peak HT‐LP metamorphism and points to an Early Permian age as most likely in line with what is observed in the Lys‐Caillaouas Massif.